‘… a highly practical thing for working and fighting…’ : the ecclesiology of G. K. Chesterton - De Santis, Anthony Nicholas (2025)
G.K. Chesterton (1874-1936) is perhaps the most widely read Anglophone lay theologian and Catholic apologist of the early twentieth century. Admired for his humor and love of adventure, he is also a profoundly irenic thinker, appealing to Anglican, Catholic, Orthodox, and Protestant readers alike. Despite Chesterton’s theological insights and achievements––one might think, for example, of his celebrated biography of St. Thomas Aquinas (1933), his defense of dogmatic Christianity in Orthodoxy (1908), or his Christocentric reading of history in The Everlasting Man (1925)––and despite, moreover, the numerous scholarly and popular books and articles which explore various aspects of his theology, Chesterton’s ecclesiology––his understanding, that is, of the nature and meaning of the Church––has been largely passed over in silence. In fact, the field of Chesterton studies has yet to yield a comprehensive, sustained analysis of his ecclesiological vision. The aim of this dissertation is to redress that gap in the secondary literature. In a word, this thesis is a scholarly and theological reconstruction of Chesterton’s ecclesiology.